Sleep quality among type 2 diabetes mellitus patients in a private hospital setting in Yangon, Myanmar. Issue 2 (1st May 2020) - Htut, Hnin Nandar; Howteerakul, Nopporn; Suwannapong, Nawarat; Rawdaree, Petch
Abstract : Purpose: This study aimed to assess the sleep quality and its associated factors among patients with type 2 diabetes mellitus (T2DM) in a private hospital in Yangon, Myanmar. Design/methodology/approach: A cross-sectional study was conducted. A total of 289 T2DM patients were interviewed using a structured questionnaire. An English version of the Pittsburgh Sleep Quality Index (PSQI) was translated into Myanmar and used for assessing sleep quality. Findings: Approximately 48.4% of T2DM patients had poor sleep quality (PSQI score > 5). The mean ± SD of the PSQI global score was 5.97 ± 3.45. About 36.0% of participants reported the presence of diabetes complications, and 14.9% used sleep medication. About 27.7% had depression and 8.3% had poor family relationships. Multiple logistic regression analysis revealed that the presence of complications (AOR = 1.86; 95%CI; 1.04–3.35), poor family relationships (AOR = 5.09; 95%CI; 1.55–16.68) and depression (AOR = 7.52; 95%CI; 3.83–14.76) were significantly associated with poor sleep quality. Originality/value: The prevalence of poor sleep quality is rather high among T2DM patients. Healthcare personnel and hospital administrators should focus on the complication status, family relationships and depression status of T2DM patients by providing regular screening for sleep quality and depression and by providing a program of sleep health education and counselling at diabetic clinics